Multi-Level security model in distributed database systems - Bakir, Cigdem; Guclu, Mehmet (PAMUKKALE UNIV, 2022)
Information security is related with efforts put in to avoid activities such as unauthorized usage, changing or disseminating of information by having access to this information. This should not be only thought as capturing of information but also as avoiding the violation of particulars such as integrity, availability, and confidentiality. Vulnerability that occurs in any one of these three basic elements will be evaluated as violation of information security. In this study, a multi-level access control method was developed. With the model proposed, in addition to the security policies offered by the Bell-LaPadula access control model, a new set of rules was defined and expanded, and a flexible and dynamic access control model was presented. The developed model being proposed in the study has been applied on data cluster which has been obtained from real life. Performance of the proposed model has been compared with the performances of Traditional Access Control models. When the obtained results were compared, it was observed that object access levels were presented more consistently and quickly with the proposed model.
Keywords: Access control; Bell-Lapuda; Security; Confidentilality; INTERNET; Engineering